PENGARUH MOTIVASI KERJA, KOMPETENSI KERJA, DAN GAYA KEPEMIMPINAN TERHADAP KINERJA KARYAWAN PADA PT. INDOPALKON PERKASA - Jennifer; Jontro Simanjuntak (SCIENTIA JOURNAL, 2022)
This study uses quantitative research methods. The method of data collection used the saturated sampling technique method. This study using SPSS 22. From that the work motivation variable is known to be 0.000 < 0.050 while for the t arithmetic value of 4.239 > t table 1.98447, means that it has a positive effect and significant effect on employee performance, the results of hypothesis testing on the work competence variable are known to be 0.000 < 0.050 while for the t arithmetic value of 4.750 > t table 1.98447, that the work competence variable has a positive and significant effect on employee performance, and the style variable leadership is known to be 0.001 < 0.050 while for the t count value of 3.330 > t table 1.98447 is accepted that has a positive and significant effect on employee performance. The results of the assessment of the calculated f value of 77.021 is greater than the f table value of 2.70, with a significance value of 0.000 <0.05. on the variables of work motivation (X1), work competence (X2) and leadership style (X3) if tested together or simultaneously have a positive and significant effect on the employee performance variable (Y).